A flow focusing microfluidic device with an integrated Coulter particle counter for production, counting and size characterization of monodisperse microbubbles. Issue 17 (2nd August 2018) - Rickel, J. M. Robert; Dixon, Adam J.; Klibanov, Alexander L.; Hossack, John A.
Abstract : An integrated micro Coulter particle counter in a flow focusing microfluidic device for electrical detection and sizing of microbubbles. Abstract : Flow focusing microfluidic devices (FFMDs) have been investigated for the production of monodisperse populations of microbubbles for chemical, biomedical and mechanical engineering applications. High-speed optical microscopy is commonly used to monitor FFMD microbubble production parameters, such as diameter and production rate, but this limits the scalability and portability of the approach. In this work, a novel FFMD design featuring integrated electronics for measuring microbubble diameters and production rates is presented. A micro Coulter particle counter (μCPC), using electrodes integrated within the expanding nozzle of an FFMD (FFMD-μCPC), was designed, fabricated and tested. Finite element analysis (FEA) of optimal electrode geometry was performed and validated with experimental data. Electrical data was collected for 8–20 μm diameter microbubbles at production rates up to 3.25 × 10 5 MB s −1 and compared to both high-speed microscopy data and FEA simulations. Within a valid operating regime, Coulter counts of microbubble production rates matched optical reference values. The Coulter method agreed with the optical reference method in evaluating the microbubble diameter to a coefficient of determination of R 2 = 0.91.